Formulasi dan Evaluasi Mutu Fisik Serta Uji Aktivitas Antiinflamasi Sediaan Balsem Stik Ekstrak Etanol Daun Bakung (Crinum asiaticum L.) - Ramadhan , Yusril; Yuniarti , Rafita; Lubis , Minda Sari; Rani , Zulmai (Journal of Pharmaceutical and Sciences, 2025)
Background: Spider lily leaves (Crinum asiaticum L.) contain bioactive compounds, such as flavonoids, which are known for their anti-inflammatory properties. Developing a convenient topical formulation like a stick balm could provide an effective and practical alternative for treating inflammation. Objective: This study aimed to formulate a stick balm containing ethanol extract of spider lily leaves (EESL) and evaluate its physical quality and anti-inflammatory activity. Methods: The extract was obtained by macerating the leaves in 96% ethanol. Stick balm formulations were prepared with varying concentrations of EESL: F0 (base), F1 (1%), F2 (3%), and F3 (5%). The physical quality of the formulations (homogeneity, pH, spreadability, melting point) was evaluated. Anti-inflammatory activity was tested on 24 male white rats induced with carrageenan. The rats were divided into six groups: negative control (induced only), positive control (commercial Geliga balm), F0, F1, F2, and F3. Paw edema volume was measured every hour for 6 hours. Results: All stick balm formulations met the physical quality standards. The anti-inflammatory test showed that the F3 formulation (5% EESL) exhibited the highest activity, with an edema reduction of 0.007 mm, which was equivalent to the positive control group (0.007 mm). The anti-inflammatory effect was concentration-dependent, with lower efficacy observed in the F2 and F1 groups. Conclusion: The ethanol extract of Crinum asiaticum L. leaves can be successfully formulated into a stable stick balm. The 5% EESL stick balm demonstrated significant anti-inflammatory activity that was comparable to a commercial product, making it a promising natural alternative for topical anti-inflammatory therapy.